“The Influence of Culture on the Disposition Effect” - Hassan, Hisham; Kishta, Mohammed; Sakhlecha, Rishabh (2013)
This paper is intended to examine, compare, and justify the degree of disposition effect present in individuals of three different cultures, Chinese, Indian and Arab. Our paper’s main objective is to investigate whether culture has a significant influence on the degree of disposition effect, that is, the fact that investors seem to hold on to their losing stocks to a greater extent than they hold their winning stocks. We examine the effect of culture on this behavioural phenomena using a devised excel program game that replicates a real stock market environment. As a control procedure, we made sure that all participants in our experiment had a background in finance and share the same demographics in terms of age, experience, and occupation (University students). Our experiment was designed to capture the degree of disposition effect exhibited using a measure that compares net realized gains to net realized losses for each participating subject. This is the same measure used by Weber and Camerer in their study of disposition effect in 1997. Using subjects from China, India, and Palestine in our experiment, we found that the disposition effect exists and is similar between all three cultures. After analysing our results further using Stata software, a statistical tool, we again found that culture does not have a significant effect on the disposition effect. However, we discovered that Chinese and Indian cultures vary the most in term of the disposition effect they exhibit. Yet, this observation is not significant given the fact that the variance is not large enough for us to conclude that culture has a substantial impact the on the disposition effect.